#### Answer

g(0)=-1

#### Work Step by Step

g(x)=$\frac{x^{2}+1}{x-1}$
g(0)=$\frac{0^{2}+1}{0-1}$
g(x)=$\frac{1}{-1}$= -1

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

g(0)=-1

g(x)=$\frac{x^{2}+1}{x-1}$
g(0)=$\frac{0^{2}+1}{0-1}$
g(x)=$\frac{1}{-1}$= -1

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.